Fast mapping of magnetic basement depth, structure and nature using aeromagnetic and gravity data: combined methods and their application in the Paris Basin. (17th April 2013) - Martelet, G.; Perrin, J.; Truffert, C.; Deparis, J.
ABSTRACT Assessment of deep buried basin/basement relationships using geophysical data is a challenge for the energy and mining industries as well as for geothermal or CO2 storage purposes. In deep environments, few methods can provide geological information; magnetic and gravity data remain among the most informative and cost‐effective methods. Here, in order to derive fast first‐order information on the basement/basin interface, we propose a combination of existing and original approaches devoted to potential field data analysis. Namely, we investigate the geometry (i.e., depth and structure) and the nature of a deep buried basement through a case study SW of the Paris Basin. Joint processing of new high‐resolution magnetic data and up‐to‐date gravity data provides an updated overview of the deep basin. First, the main structures of the magnetic basement are highlighted using Euler deconvolution and are interpreted in a structural sketch map. The new high‐resolution aeromagnetic map actually offers a continuous view of regional basement structures and reveals poorly known and complex deformation at the junction between major domains of the Variscan collision belt. Second, Werner deconvolution and an ad hoc post‐processing analysis allow the extraction of a set of magnetic sources at (or close to) the basin/basement interface. Interpolation of these sources together with the magnetic structural sketch provides a Werner magnetic basement map displaying realistic 3D patterns and basement depths consistent with data available in deep petroleum boreholes. The last step of processing was designed as a way to quickly combine gravity and magnetic information and to simply visualize first‐order petrophysical patterns of the basement lithology. This is achieved through unsupervised classification of suitably selected gravity and magnetic maps and, as compared to previous work, provides a realistic and updated overview of the cartographic distribution of density/magnetization of basement rocks. Altogether, the three steps of processing proposed in this paper quickly provide relevant information on a deep buried basement in terms of structure, geometry and nature (through petrophysics). Notwithstanding, limitations of the proposed procedure are raised: in the case of the Paris Basin for instance, this study does not provide proper information on Pre‐Mesozoic basins, some of which have been sampled in deep boreholes.